Fake news, French Law and democratic legitimacy: lessons for the United Kingdom?. Issue 1 (2nd January 2019) - Craufurd Smith, Rachael
ABSTRACT: The United Kingdom is currently examining far-reaching regulatory proposals designed to address the online transmission of harmful content, including disinformation. Of particular interest, therefore, is French Law no. 2018–1202 on the 'fight against the manipulation of information'. The French Law establishes a fast-track civil procedure to tackle the transmission of false information prior to key elections and referenda; addresses foreign state-funded broadcast propaganda; and seeks to enhance transparency regarding the financing and distribution of online content. Restrictions on the transmission of information, particularly in the run-up to elections, are inherently suspect and the Conseil constitutionnel carefully reviewed the French proposals to ensure that any constraints on freedom of expression were both justified and necessary. French Law 2018–1202 thus offers an example of a rather 'muscular' form of intervention in the election field, but one which seeks to preserve democratic legitimacy without undermining the individual freedoms on which it rests.